Impact of soil and water conservation measures on catchment hydrological response: a case in north Ethiopia - Nyssen, Jan; Clymans, W.; Descheemaeker, Katrien K.; Poesen, J.; Vandecasteele, I.; Vanmaercke, M.; Zenebe, A.; Camp, M. van; Haile, M.; Haregeweyn, Nigussie; Moeyersons, J.; Martens, K.; et al. (Wiley, 2010)
Impact studies of catchment management in the developing world rarely include detailed hydrological components. Here, changes in the hydrological response of a 200-ha catchment in north Ethiopia are investigated. The management included various soil and water conservation measures such as the construction of dry masonry stone bunds and check dams, the abandonment of post-harvest grazing, and the establishment of woody vegetation. Measurements at the catchment outlet indicated a runoff depth of 5 mm or a runoff coefficient (RC) of 1?6% in the rainy season of 2006. Combined with runoff measurements at plot scale, this allowed calculating the runoff curve number (CN) for various land uses and land management techniques. The pre-implementation runoff depth was then predicted using the CN values and a ponding adjustment factor, representing the abstraction of runoff induced by the 242 check dams in gullies. Using the 2006 rainfall depths, the runoff depth for the 2000 land management situation was predicted to be 26?5 mm (RC D 8%), in line with current RCs of nearby catchments. Monitoring of the ground water level indicated a rise after catchment management. The yearly rise in water table after the onset of the rains ( T) relative to the water surplus (WS) over the same period increased between 2002-2003 ( T/WS D 3?4) and 2006 ( T/WS >11?1). Emerging wells and irrigation are other indicators for improved water supply in the managed catchment. Cropped fields in the gullies indicate that farmers are less frightened for the destructive effects of flash floods. Due to increased soil water content, the crop growing period is prolonged. It can be concluded that this catchment management has resulted in a higher infiltration rate and a reduction of direct runoff volume by 81% which has had a positive influence on the catchment water balance.